2022
DOI: 10.3390/children9081215
|View full text |Cite
|
Sign up to set email alerts
|

What Do Mothers (or Caregivers) Know about Their Children’s Oral Hygiene? An Update of the Current Evidence

Abstract: Tooth decay remains one of the most common diseases in children, although it is a preventable injury and despite significant advances that has been made in terms of attention and care for oral hygiene. Several studies have shown the association between prevalence of tooth decay in children and parents’ incorrect oral care habits, with a low educational level and a low socioeconomic background. The question that arises concerns the actual oral hygiene knowledge of mothers, fathers, family members or caregivers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…The final section of questions on children's oral health behavior consisted of the following five questions: one question on oral hygiene, two questions on diet, and two questions on dental attendance and utilization. Mothers do serve as a reliable source to seek out the oral health behavior of children, as substantiated by previous literature [13]. Response to questions on oral health behavior was the dependent variable in the study.…”
Section: Components and Variablesmentioning
confidence: 84%
See 1 more Smart Citation
“…The final section of questions on children's oral health behavior consisted of the following five questions: one question on oral hygiene, two questions on diet, and two questions on dental attendance and utilization. Mothers do serve as a reliable source to seek out the oral health behavior of children, as substantiated by previous literature [13]. Response to questions on oral health behavior was the dependent variable in the study.…”
Section: Components and Variablesmentioning
confidence: 84%
“…Mothers' sense of coherence has been shown to have a bearing on the oral health behavior and quality of life of the children. Even though the limitation of such studies is that they are self-reported, it is still a reliable way to analyze, as assessed and recommended by previous studies [11,13,27].…”
Section: Discussionmentioning
confidence: 99%
“…The present study treated patients by scaling and root planing, prophylaxis, education, and oral hygiene instructions, significantly improving periodontal health. Future studies would be advisable to determine the composition of the periodontal microbiota in these patients, to know the cytokine profile involved in the immune response and to compare it with healthy patients, as well as to study some genetic variants that could be risk factors or genetic protectors against the development of periodontal disease [ 55 , 56 ]. .…”
Section: Discussionmentioning
confidence: 99%
“…According to the recommendations of the American Academy of Paediatric Dentistry (AAPD) and the European Academy of Paediatric Dentistry (EAPD), the role of caregivers is to assist and perform good oral hygiene practices in children under the age of six [ 12 ]. However, the percentage of caregivers who do not supervise and assist their children during brushing is very high [ 13 ]. It has been observed that mothers have a key role in shaping good oral hygiene practices in children [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The more importance mothers attach to their own oral hygiene, the higher the frequency of brushing in their children [ 15 ]. As research shows, many mothers-to-be lack sufficient knowledge of the risk factors and importance of ECC prevention, due to, for example, inappropriate attitudes toward oral hygiene and lack of institutional support, as well as insufficient information from health professionals [ 13 ].…”
Section: Introductionmentioning
confidence: 99%